Outcomes following brachytherapy boost for intermediate- and high-risk prostate cancer: A retrospective bicenter study by the SFRO brachytherapy group. (March 2023) - Ka, Kanta; Schiappa, Renaud; Terlizzi, Mario; Mallet, Frederic; Martin, Etienne; Chand, Marie-Eve; Demogeot, Nicolas; Peiffert, Didier; Pommier, Pascal; Quivrin, Magali; Kissel, Manon; Pasquier, Corentin; et al.
Highlights: Largest French series on HDD brachytherapy boost for prostate cancer. The quality of the data collection is one of its strengths. This study shows the efficacy of HDD brachytherapy boost in intermediate and high risk prostate cancers at the national level and a homogeneity of practices in France. Abstract: Introduction: Radiotherapy dose escalation improves biochemical control in intermediate- or high-risk prostate cancer. Brachytherapy boost was shown to further improve biochemical control compared to radiotherapy alone in three randomized trials. The SFRO brachytherapy group sought to evaluate the efficacy and toxicity of BT-boost for intermediate and high-risk prostate cancer in real life, and to determine prognostic factors for efficacy and toxicity. Material and method: A retrospective study was conducted, including all patients with intermediate- or high-risk prostate cancer treated with a combination of external beam radiotherapy (EBRT) and high dose-rate brachytherapy boost (HDR-BB), from 2006 until December 2019 at two centers. Patient characteristics, initial disease, treatment and follow-up were collected. Results: 709 patients from two centers were analyzed given a short follow-up in the other centers. Out of those, 277 were intermediate risk (170 favorable and 107 unfavorable) and 432 were high risk. The median EBRT and HDR-BB doses were 46 Gy (35–50) and 14 Gy (10–20). After a median follow-up of 62 months, biochemical control at 5 years was 87.5 % for the overall population, 91 % and 85 % for intermediate- and high-risk cancers, respectively. At 5 years, biochemical and clinical relapse-free survival, metastasis-free survival and local control rates were 83 %, 90 % and 97 % respectively. 5-years overall survival was 94 %. Late grade 2 or higher GU or GI toxicity was found in 36 patients (5 %) and 9 patients (1.3 %). Conclusion: This bicenter analysis shows the efficacy and tolerability of HDR-BB as a complement to external radiotherapy. Further improvements such as combination with new hormonal agents or new brachytherapy-radiotherapy fractionation regimens are warranted to improve further the outcomes and therapeutic ratio.